The Effectiveness of Narrative Writing Text Learning by Using Direct Instructional Models and ARIAS Models Based on Learning Styles for VII Grade Junior High School Students - Yuliannurunnisa, Wahyutia; Supratman, Suparmin Dandan; Nuryatin, Agus (Pascasarjana Universitas Negeri Semarang, 2018)
The purpose of this research is to examine the effectiveness of learning to present the creative ideas in the form of narrative text using direct instruction models and ARIAS models based on learning styles of students of class VII junior high school. So far, the learning process of writing is still theoretical, emphasizing aspects of knowledge and understanding only, the teacher in using the learning model is still less than optimal, while the aspect of practice has not gotten the teacher's attention. The results of this research can prove the effectiveness of the use of direct instruction models and ARIAS models for students who are visual and auditory learning styles so that their learning outcomes are optimal. The method used in this research is quasi-experimental. Research data collection techniques using test instruments of narrative text writing skills, learning style tests, and observations. Normality test using Kolmogorov Smirnov test on SPSS 16 program, a test of Levene test homogeneity, and hypothesis testing with 2x2 variant analysis. The conclusions of the results of this research are (1) the use of direct instruction models is more effective for students who have an auditory learning style and the use of the ARIAS model is more effective for students who have a visual learning style, (2) narrative text writing skills of students who have auditory learning styles are different from students' narrative text writing skills who have a visual learning style, (3) learning models and learning styles of students influence the writing skills of narrative text of VII grade junior high school students.